THE EFFECT OF PROBLEM BASED LEARNING (PBL) COMBINED WITH COOPERATVE LEARNING JIGSAW IN TERMS OF MATHEMATICAL COMMUNICATION SKILL AND STUDENT'S ACHIEVEMENT GRADE 11TH SCIENCE SMA N 2 YOGYAKARTA - Valeria Kartikaningtyas Valeria Kartikaningtyas; Heri Retnawati Heri Retnawati (Universitas Negeri Yogyakarta, 2016)
The aim of this study was to know about the effect of Problem Based Learning (PBL) combined withcooperative learning Jigsaw in terms of mathematical communication skill and student's achievement inmathematics grade 11th Science SMA Negeri 2 Yogyakarta. The research method is quasi experiment which usedone experiment group and one control group. The data were collected through a mathematical communication andstudent's achievement tests, questionnaire for oral communication in mathematics learning, and observation formfor learning activities and student's communication. The results of the study showed that (1) PBL-Jigsaw is notbetter than scientific approach in student's mathematical communication skill, (2) PBL-Jigsaw is not better thanscientific approach in student's achievement, and (3) there was a significant correlation, 0.618, betweenmathematical communication skills and student's achievement.